2014
DOI: 10.1161/jaha.114.000921
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Histological Assessment of an Experimental Model of Takotsubo's Cardiomyopathy

Abstract: BackgroundOur objectives were to characterize functional and structural features of an experimental model of Takotsubo cardiomyopathy, and its response to beta‐blockers.Methods and ResultsIn protocol 1, a dose‐finding study: 69 rats received various doses of isoproterenol (ISO) and echocardiographic and histologic parameters were measured on days 2 to 3 or day 8. There were no dose‐dependent effects and, out of 69 ISO‐treated rats, 40 (58.0%) survived and 29 (42.0%) died within 24 hours. Of survivors, 30 had a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
60
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 16 publications
3
60
2
Order By: Relevance
“…EBD uptake is further associated with loss of membrane integrity and loss of mitochondrial membrane potential 33, 34 . Myocardial necrosis after ISO administration has been reported in several animal models 5, 10, 23, 24, 35, 36 , but we did not find global functional defects or cardiac fibrosis. Therefore, we questioned if EBD + myocytes were indeed all destined for necrosis.…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…EBD uptake is further associated with loss of membrane integrity and loss of mitochondrial membrane potential 33, 34 . Myocardial necrosis after ISO administration has been reported in several animal models 5, 10, 23, 24, 35, 36 , but we did not find global functional defects or cardiac fibrosis. Therefore, we questioned if EBD + myocytes were indeed all destined for necrosis.…”
Section: Discussioncontrasting
confidence: 81%
“…In an earlier 2007 study in rats, Ellison et al 23 reported that a single subcutaneous ISO (5mg/kg) injection induced acute LV failure at 1 day with full recovery by 6 days. Sachdeva et al 24 described a “takotsubo-like” cardiomyopathy in rats after a single subcutaneous injection that used a 20-fold higher concentration than used by Ellison et al 23 . In mice, Shao et al 25 demonstrated LV systolic dysfunction 1 day after intraperitoneal injection of 400 mg/kg ISO.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, this case study indicated a decline in the apex LV wall motion that mimics Takotsubo cardiomyopathy. Sachdeva et al showed that an experimental model of Takotsubo cardiomyopathy presents persistent foci of necrosis and fibrosis [4]. Izgi et al reported myocardial edema as one of the characteristic features in the pathogenesis of Takotsubo syndrome [5].…”
Section: Discussionmentioning
confidence: 99%
“…These findings have also been observed in the animal models of TTS where histological abnormalities persist despite normalization of the LV ejection fraction. 52 Furthermore, there is a clear association between the ongoing symptoms in patients with TTS at 3 months and chemical and imaging myocardial abnormalities. 24 At the moment, there is no evidence-based therapy for chronic management of patients with TTS.…”
Section: D) the "Recovery" Phasementioning
confidence: 99%